The Correlation of Mother’s Knowledge About Diarrhea and Hand Wash Behavior With Diarrhea Event In Toddlers In Sidomulyo Health Center Pekanbaru City Year 2018 - Ratih Ayuningtiyas; Cherlina Cherlina; Diny Supriana Wirdatul Thoibah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
. Background : Diarrhea is deflation with washy or half washy feces more than usual, more than 200 gram or 200 ml/24 hours or washy defecation with/with out mucus and blood. Most of death in diarrhea suspected cause of lack of community knowledge, especially mother, about prevention and management of diarrhea. Some research found that hand wash with soap can trim the number of diarrhea patiens. Parents’ Knowledge and awareness to their toddler’s health problem very important so that toddler stay healthy and avoid from diarrhea. Health Care Inpatient Sidomulyo is a health care for community who live in Tampan District. Based on Department if Health Riau Province in January 2017 there are 226 cases of diarrhea in toddlers that consist of 139 cases of diarrhea in toddler boys and 87 cases of diarrhea in toddler girls. Tampan District has the highest incidence in toddlers in January 2017. Objective : To know the correlation mother’s knowledge about diarrhea and hand wash behavior with incidence of diarrhea in toddlers in Health Care Inpatient Sidomulyo, Pekanbaru City. Method : This study is using analytic correlation observational study with cross-sectional approach. Way to get the sample using Accidental Sampling technic. Data obtained then analyzed using Spearman.Result : There is a significan correlation between mother’s knowledge about diarrhea with incidence of diarrhea on toddlers in Health Care Inpatient Sidomulyo with p value <0,05 is 0,015 and significant correlation between mother’s hand wash behavior with incidence of diarrhea in toddlers in Health Care Inpatient Sidomulyo with p value <0,05 is 0,001. Conclusion : There is significant correlation between mother’s knowledge about diarrhea and mother’s hand wash behavior to incidence of diarrhea in toddlers in Health Care Inpatient Sidomulyo